Aviation Criminal Law Regulations of the Tokyo Convention and the Penal Code to Counteract Terrorist Acts - Mendala, Oliwier; Tokarska, Katarzyna (Journal of KONBiN, 2021)
The aim of the study is to present issues related to acts of terror and attempts to counteract them, whose subject matter of which is governed by a number of legal acts of various territorial scope, primarily by regulations contained in the Tokyo Convention, which is a source of public international law, and Polish normative acts, such as the Aviation Law together with legal and penal regulations. The paper presents considerations aimed at indicating the proper interpretation of the provisions regulating the obligation to undertake investigative and explanatory actions as part of pre-trial proceedings conducted by the prosecutor, the issues of jurisdiction and competence of the courts adjudicating in criminal cases, and the issues concerning the institution of extradition and its legal basis.